Problem Indicators of Drug Management at Distribution Stage in Indonesian Hospitals: A Literatur Review - Putri, Wiwin Nopita; Yasin, Nanang Munif; Endarti, Dwi (Generics: Journal of Research in Pharmacy, 2024)
The distribution stage is an important part of drug management in hospitals. However, there are problems with the indicators of the drug distribution stage in hospitals. Thus, the purpose of this study is to determine the problems in distribution indicators in hospital pharmaceutical installations based on indicators the Ministry of Health the Republic of Indonesia (2008), Pudjaningsih (1996) and WHO (1993). A literatur search performed in October 2023 using Google Schloar, researchgate and Garuda Kemendikbud. Methodological quality was assessed using tools from the Joanna Briggs Institute (JBI). We retrieved 3.237 articles and included eight studies. Regarding the design, they were observation documen retrospective (n=8). It was found that there were problems in the distribution stage indicators, such as turn over ratio, expired or damaged drugs, dead drug stocks and drug availability that was not optimal in hospitals. Most articles report discrepancies in drug distribution indicators based on WHO (1993), Ministry of Health (2008) and Pudjaningsih (1996). This shows that drug management in hospitals is not optimal. The findings of this study may be of interest to pharmacists, doctors and other health workers to pay attention to the smooth cooperation of drug management in hospitals.